Spatial resolution analysis of passive bistatic radar using low-orbit navigation augmented signals. Issue 1 (1st November 2022) - Wang, Jinbo; Fu, Hongwei; Wang, Binbin; Liu, Liguo
Abstract : Aiming at the problem that the traditional monostatic ambiguity function is inconvenient to analyze the spatial resolution of the passive bistatic radar, this paper proposes a method to analyze it in a given airspace by using the spatial distribution of the ambiguity function. This method converts the time-delay Doppler distribution of the traditional ambiguity function into the spatial distribution near the reference target, which makes it more suitable for the intuitive analysis of the spatial resolution capability of the passive bistatic radar. This new method is used to analyze the target resolution capability in the designated airspace when Navigation augmented signals transmitted by the low-orbit communication satellite is used as the illuminator of opportunity. The distribution of the ambiguity function is transformed from a pushpin shape under the monostatic time delay-Doppler shift to a flat "sandwich biscuit" shape in space. The shape is closely related to the geometric relationship of the bistatic radar. Through the spatial distribution of the ambiguity function, the target resolution in a given airspace can be directly observed, which is convenient for analyzing the spatial resolution capability of the signal under different spatial geometric relationships. This also provides convenience for the optimal selection of the location of the illuminator of opportunity and receiving station.